MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN PENDEKATAN RECIPROCAL TEACHING - Fitry Wahyuni (MES: Journal of Mathematics Education and Science, 2019)
Abstract. This study aims to (1) improve students' mathematical communication skills through the STAD Type Cooperative Learning Model with the Reciprocal Teaching Approach in MTs Islamiyah Medan, (2) describe the process of implementing the STAD Type Cooperative Learning Model with the Reciprocal Teaching Approach at MTs Islamiyah Medan. This research is a class action research with 31 students of VII-2 MTs Islamiyah Medan subject. Instruments used include learning implementation observation sheets, mathematical communication observation sheets, and mathematical communication test questions. Implementation of the STAD Cooperative Learning Model with the Reciprocal Teaching Approach includes: (1) Initial Activities: the teacher conveys apperception and motivation regarding the material to be studied; (2) this activity: group work which includes Clarifying discussion, Predicting discussion Questioning discussion, Summarizing discussion, discussion of LKS questions, and group percentage; (3) Closing: the teacher together with students draw conclusions on the material that has been learned. After learning takes place there is an increase in students' mathematical communication skills. This can be seen from the results of observations of the implementation of learning an increase in the percentage from cycle I to cycle II amounted to 90.90% to 94.45% with a very good category of accuracy. Furthermore, the results of observations of students' mathematical abilities also increased from cycle I by 75.00% (good category) to 82.41% (good category) in the second cycle. This is in line with the results of a mathematical communication test that has increased after the second cycle, which is as many as 27 students or 64.52% of the number of students in class VII-2 has increased in total scores to good categories.Keywords: Mathematical Communication, Cooperative, STAD, Reciprocal Teaching.